Potential Airborne Releases and Deposition of Radionuclides from the Santa Susana Field Laboratory during the Woolsey Fire. Issue 4 (8th April 2023) - Rood, Arthur S.; Mohler, H. Justin; Grogan, Helen A.; Mangini, Colby; Caffrey, Emily A.; Till, John E.
Abstract: The Santa Susana Field Laboratory (SSFL), located in southern California, is a former research facility, and past activities have resulted in residual radioactive contamination in Area IV of the Site. The Woolsey Fire burned across the site, including some of the contaminated areas, on 8–11 November 2018. Atmospheric transport modeling was performed to determine where the smoke plume went while the fire burned across the SSFL and the deposition footprint of particulates in downwind communities. Any radionuclides on vegetation and in surface soil released by the fire were assumed to follow particulate matter transport path and deposition. The predicted deposition footprint was used to guide confirmatory soil sampling at 16 locations including background. Highest offsite deposition was determined to be northeast of the Oak Park community, which is located about 6 km southwest of SSFL. Depth-profile sampling was used to evaluate whether radionuclides of SSFL origin were potentially emitted and deposited during the Woolsey Fire. If radionuclides had been deposited from the Woolsey Fire at sufficient concentrations, then they would be detected in the surface layer and would be expected to be higher within the plume footprint than outside it. An upper bound estimate of the hypothetical effective dose to a person in Oak Park based on measured radionuclide concentrations in soil and vegetation on the SSFL was less than 0.0002 mSv. The occurrence of naturally occurring radionuclides at concentrations above the established background for the SSFL was attributed to natural variability in geologic formations and not SSFL. No anthropogenic radionuclides were measured at levels above those expected from global fallout. The soil sampling confirmed that no detectable levels of SSFL-derived radionuclides migrated from SSFL at the locations sampled because of the Woolsey Fire or from past operations of the SSFL.